Stafne's Defect with Buccal Cortical Expansion: A Case Report. (4th May 2010) - Flores Campos, Paulo Sérgio; Oliveira, José Aloysio Carvalho; Dantas, Janaina Araújo; de Melo, Daniela Pita; Pena, Nilson; Santos, Luís Antônio Nogueira; Crusoé-Rebello, Iêda Margarida Rocha
Abstract : A rare case of Stafne's bone cavity, type III-G, is reported in a 49-year-old male patient who had been referred to a private clinic for a routine evaluation. The final diagnosis was based on computed tomography. Scintigraphy played a fundamental role in determining the most likely etiology.